Schiff Base liquid Crystals with Terminal Alkoxy Group Synthesis and Thermotropic Properties. - Jber, Nasreen R; Shukur, Mohammad M; Najaf, Ahmed A (Al-Nahrain Journal of Science, 2018)
A new homologous series of Schiff base esters comprising a terminal alkoxy substituent N-(n-alkoxy-4``-bezoyloxy)-4`- benzylidene-4-butyl aniline was studied. The alkyloxy substituent contributes to the molecular polarizability, thus, affecting intermolecular interactions, hence, resulting in nematic polymorphism. The mesomorphic properties were studied using polarizing optical microscope (POM). The lower members, n-methoxy and n-ethoxy derivatives were non-mesogens, enantiotropic nematogenic phase was observed on further lengthening of the alkyl chain from C3 to C6 and smectogenic phase was observed for compounds C7 and C8. FT-IR, 1HNMR, 13CNMR, EI-MS and elemental analysis were employed to elucidate the molecular structure of the title compounds whereas the liquid crystal properties were determined by POM analysis. The mesomorphic behaviors of the homologous compounds are rationalized based on the varying lengths of the alky chain.